Selective Attention in Cross-Situational Statistical Learning: Evidence From Eye Tracking - Yu, Chen; Zhong, Yiwen; Fricker, Damian (Frontiers in Psychology, 2012)
A growing set of data show that adults are quite good at accumulating statistical evidence across individually ambiguous learning contexts with multiple novel words and multiple novel objects (Fitneva & Christiansen, 2011; Kachergis, Yu, & Shiffrin, 2012; Yu & Smith, 2007; Yurovsky, Fricker, Yu, & Smith, under resubmission); experimental studies also indicate that infants and young children do this kind of learning as well (Smith & Yu, 2008; Vouloumanos & Werker, 2009). The present study provides evidence for the operation of selective attention in the course of cross-situational learning with two main goals. The first was to show that selective attention is critical for the underlying mechanisms that support successful cross-situational learning. The second one was to test whether an associative mechanism with selective attention can explain momentary gaze data in cross-situational learning. Toward these goals, we collected eye movement data from participants when they engaged in a cross-situational statistical learning task. Various gaze patterns were extracted, analyzed and compared between strong learners who acquired more word-referent pairs through training, and average and weak learners who learned fewer pairs. Fine-grained behavioural patterns from gaze data reveal how learners control their attention after hearing a word, how they selectively attend to individual objects which compete for attention within a learning trial, and how statistical evidence is accumulated trial by trial, and integrated across words, across objects, and across word-object mappings. Taken together, those findings from eye movements provide new evidence on the real-time statistical learning mechanisms operating in the human cognitive system.